Conductive silicon carbide-based ceramic and preparation method thereof
By adding multi-walled carbon nanotubes, titanium boride and tungsten carbide to silicon carbide, forming a conductive network and improving fracture toughness, the problem of insufficient conductivity of silicon carbide-based ceramics is solved, and its performance in the fields of electric spark processing, semiconductor devices and high-temperature heating elements is significantly improved.
Patent Information
- Application Number
- CN202411909033.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
The existing silicon carbide-based ceramics have insufficient electrical conductivity, which affects their performance in the fields of electric spark processing, semiconductor devices and high-temperature heating elements.
By adding multi-walled carbon nanotubes, titanium boride and tungsten carbide to silicon carbide-based ceramics, a conductive network is formed to improve the conductivity of the material, and the fracture toughness of the material is improved through mechanisms such as bridging, deflection and plastic transformation.
The conductive properties and fracture toughness of silicon carbide-based ceramics are significantly improved, and their application performance in high temperature and high pressure environments are enhanced.
Smart Images

Figure CN119684007A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of silicon carbide ceramics, and specifically to a conductive silicon carbide-based ceramic and a preparation method thereof. Background Art
[0002] Silicon carbide-based ceramics are a type of inorganic non-metallic material that is resistant to high temperatures and has strong stability. They are widely used in aerospace, metallurgy, semiconductors, and chemical industries. In particular, their electrical conductivity is crucial in electrospark machining, semiconductor devices, and high-temperature heating elements. In these applications, the excellent electrical conductivity of conductive silicon carbide-based ceramics can reduce energy loss, improve processing efficiency and thermal efficiency, and directly affect the performance of semiconductor devices. Therefore, improving the electrical conductivity of silicon carbide-based ceramics is a problem that needs to be solved at present. Summary of the invention
[0003] In view of the above problems, the embodiments of the present application provide a conductive silicon carbide-based ceramic and a preparation method thereof, which improves the conductivity of the silicon carbide-based ceramic.
[0004] According to one aspect of an embodiment of the present application, a conductive silicon carbide-based ceramic is provided, comprising: silicon carbide, multi-walled carbon nanotubes, titanium boride and tungsten carbide, wherein the content of the multi-walled carbon nanotubes is 0.5-3wt% of the silicon carbide, the content of the titanium boride is 2-12wt% of the silicon carbide, and the content of the tungsten carbide is 2-12wt% of the silicon carbide.
[0005] In an optional manner, the content of the multi-walled carbon nanotubes is 1-1.5wt% of the silicon carbide, the content of the titanium boride is 4-6wt% of the silicon carbide, and the content of the tungsten carbide is 4-6wt% of the silicon carbide.
[0006] In an optional manner, the content of the multi-walled carbon nanotubes is 1wt% of the silicon carbide, the content of the titanium boride is 4wt% of the silicon carbide, and the content of the tungsten carbide is 4wt% of the silicon carbide; or, the content of the multi-walled carbon nanotubes is 1.5wt% of the silicon carbide, the content of the titanium boride is 6wt% of the silicon carbide, and the content of the tungsten carbide is 6wt% of the silicon carbide.
[0007] In an optional manner, the conductive silicon carbide-based ceramic also includes a binder, a dispersant and a lubricant, wherein the content of the binder is 8wt% of the silicon carbide, the content of the dispersant is 3wt% of the silicon carbide, and the content of the lubricant is 5wt% of the silicon carbide.
[0008] In an optional manner, the conductive silicon carbide-based ceramic further includes boron carbide, and the content of the boron carbide is 2 wt % of the silicon carbide.
[0009] According to another aspect of an embodiment of the present application, a method for preparing a conductive silicon carbide-based ceramic is provided, comprising the following steps:
[0010] S100, using silicon carbide powder, multi-walled carbon nanotube powder, titanium boride powder, tungsten carbide powder, a binder, a dispersant and a lubricant as raw materials, using anhydrous ethanol as a solvent, and ball milling in a ball mill to obtain a slurry, wherein the content of the multi-walled carbon nanotube is 0.5-3wt% of the silicon carbide, the content of the titanium boride is 2-12wt% of the silicon carbide, the content of the tungsten carbide is 2-12wt% of the silicon carbide, the content of the binder is 8wt% of the silicon carbide, the content of the dispersant is 3wt% of the silicon carbide, the content of the lubricant is 5wt% of the silicon carbide, and the mass of the anhydrous ethanol is the same as the total mass of the four powders of the silicon carbide powder, the multi-walled carbon nanotube powder, the titanium boride powder and the tungsten carbide powder;
[0011] S200, drying, crushing, sieving and granulating the slurry to obtain ceramic powder;
[0012] S300, dry-pressing the ceramic powder to obtain a green body;
[0013] S400, sintering the green blank in a sintering furnace to obtain a conductive silicon carbide-based ceramic.
[0014] In an optional manner, the particle size of the silicon carbide powder is 0.5-0.7 microns, the particle size of the multi-walled carbon nanotube powder is less than or equal to 7 microns, the particle size of the titanium boride powder is 0.8-1.2 microns, and the particle size of the tungsten carbide powder is 0.8-1.2 microns.
[0015] In an optional manner, the content of the multi-walled carbon nanotubes is 1wt% of the silicon carbide, the content of the titanium boride is 4wt% of the silicon carbide, and the content of the tungsten carbide is 4wt% of the silicon carbide; or, the content of the multi-walled carbon nanotubes is 1.5wt% of the silicon carbide, the content of the titanium boride is 6wt% of the silicon carbide, and the content of the tungsten carbide is 6wt% of the silicon carbide.
[0016] In an optional manner, in S100, boron carbide is further added during ball milling in the ball mill, and the content of the boron carbide is 2 wt % of the silicon carbide.
[0017] In an optional manner, the ball milling time in S100 is 48 hours;
[0018] In the S200, the slurry is dried in a vacuum drying oven at 90° C. for 6 hours, and then manually crushed, sieved and granulated, with a sieve of 80 meshes, to obtain ceramic powder;
[0019] In the S400, the green blank is sintered in an ultra-high temperature vacuum sintering furnace at a sintering temperature of 2150° C. and kept at this temperature for 1 hour to obtain a conductive silicon carbide-based ceramic.
[0020] The present invention enhances the conductivity of the prepared conductive silicon carbide-based ceramic by adding a ternary composite phase with conductive properties, specifically multi-walled carbon nanotubes, titanium boride and tungsten carbide, three second-phase materials with excellent conductive properties, based on the first-phase material of silicon carbide. Furthermore, the fracture toughness of the conductive silicon carbide-based ceramic is also improved.
[0021] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION
[0022] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0023] Silicon carbide-based ceramics are an advanced inorganic non-metallic material that is usually prepared by a high-temperature sintering process. The crystal structure of silicon carbide-based ceramics allows them to remain stable in many extreme environments. Silicon carbide-based ceramics have a wide range of applications, such as being used to manufacture high-temperature structural components and engine components in the aerospace field, as lining materials to build high-temperature furnaces in the metallurgical industry, as substrates or heat sinks for semiconductor devices, as materials for cutting tools and abrasives in the mechanical processing field, and for corrosion-resistant and wear-resistant containers and pipes in the chemical industry, etc.
[0024] In some application fields, such as EDM, semiconductor devices and high-temperature heating elements, silicon carbide-based ceramics need to be conductive. For example, in EDM, conductive silicon carbide-based ceramics can be used as tool electrodes, and precision machining can be performed using their conductivity and high temperature resistance; in semiconductor devices, conductive silicon carbide-based ceramics can be used as substrates for semiconductor devices; in high-temperature heating elements, conductive silicon carbide-based ceramics can withstand high temperatures and effectively conduct current, and can be used for heating and temperature control.
[0025] In the above application scenarios, the excellent conductivity of conductive silicon carbide-based ceramics can improve application performance. For example, in fields such as electrical discharge machining, the good conductivity of silicon carbide-based ceramics can reduce resistance, reduce energy loss, and improve processing efficiency; in high-temperature heating elements, the excellent conductivity of silicon carbide-based ceramics helps reduce heat loss and improve thermal efficiency; in semiconductor devices, the conductivity of silicon carbide-based ceramics directly affects the electrical properties of the device, such as switching speed and power handling capacity.
[0026] Therefore, how to improve the conductivity of silicon carbide-based ceramics is an urgent problem to be solved.
[0027] Based on this, the present application provides a conductive silicon carbide-based ceramic, which is based on the first phase material of silicon carbide, and adds a ternary complex phase with conductive properties, specifically multi-walled carbon nanotubes, titanium boride and tungsten carbide, three second phase materials with excellent conductive properties, to enhance the conductive properties of the prepared conductive silicon carbide-based ceramic. Furthermore, the fracture toughness of the conductive silicon carbide-based ceramic is also improved.
[0028] The embodiment of the present application provides a conductive silicon carbide-based ceramic, including silicon carbide (SiC) powder, multi-walled carbon nanotube (MWCNT) powder, titanium boride (TiB2) powder and tungsten carbide (WC) powder. The content of multi-walled carbon nanotube is 0.5-3wt% of silicon carbide, the content of titanium boride is 2-12wt% of silicon carbide, and the content of tungsten carbide is 2-12wt% of silicon carbide.
[0029] Among them, silicon carbide is the first phase material and is the base material of silicon carbide-based ceramics.
[0030] Multi-walled carbon nanotubes, titanium boride and tungsten carbide are second-phase materials with excellent electrical conductivity. By doping the above materials in silicon carbide, the electrical conductivity of silicon carbide-based ceramics can be significantly improved. Among them, multi-walled carbon nanotubes have good electrical conductivity. Due to their special graphene curled structure, multi-walled carbon nanotubes can form a three-dimensional network in the ceramic matrix to provide a conduction path for electrons. Electrons can move freely on the wall of multi-walled carbon nanotubes to form a conductive network, thereby significantly improving the overall electrical conductivity of silicon carbide-based ceramics. Titanium boride is a semiconductor material. Although its electrical conductivity is not as good as that of metals, it is much higher than that of silicon carbide. Adding titanium boride can improve the electrical conductivity of silicon carbide-based ceramics to a certain extent; in addition, titanium boride powder can improve the characteristics of grain boundaries and reduce the obstacles of grain boundaries to electron transmission, thereby improving the overall electrical conductivity of the material. Tungsten carbide is a material with metallic properties. Its conductivity is much higher than that of silicon carbide. Adding tungsten carbide can act as a conductive phase to provide an electron conduction channel. In addition, tungsten carbide powder can form contact points in the ceramic matrix. These contact points help the flow of electrons, thereby improving the conductivity of silicon carbide-based ceramics.
[0031] Multi-walled carbon nanotubes have extremely high strength and modulus. When cracks extend, carbon nanotubes can form bridges on the crack surface to prevent further crack extension. This bridging effect can effectively transfer and disperse stress, thereby improving the fracture toughness of the material. Titanium boride can play a similar bridging role at the crack tip, connecting the two surfaces of the crack to prevent crack extension; in addition, when the crack encounters hard particles such as titanium boride, the crack path will be deflected, increasing the crack extension path, thereby consuming more energy and improving fracture toughness. Tungsten carbide has high plasticity. When the crack tip encounters tungsten carbide particles, the particles can absorb energy through plastic deformation, thereby improving the fracture toughness of the material. Therefore, by adding second phase materials such as multi-walled carbon nanotubes, titanium boride and tungsten carbide to silicon carbide, these additives can prevent crack extension through crack bridging, crack deflection, plastic deformation and other mechanisms, thereby improving the material's resistance to fracture and effectively improving the material's fracture toughness.
[0032] Preferably, the content of multi-walled carbon nanotubes is 1-1.5wt% of silicon carbide, the content of titanium boride is 4-6wt% of silicon carbide, and the content of tungsten carbide is 4-6wt% of silicon carbide. The conductive silicon carbide-based ceramics with the above ratios have better conductivity.
[0033] Further preferably, the content of multi-walled carbon nanotubes is 1wt% of silicon carbide, the content of titanium boride is 4wt% of silicon carbide, and the content of tungsten carbide is 4wt% of silicon carbide; or, the content of multi-walled carbon nanotubes is 1.5wt% of silicon carbide, the content of titanium boride is 6wt% of silicon carbide, and the content of tungsten carbide is 6wt% of silicon carbide. The conductive silicon carbide-based ceramics with the above ratios have better material conductivity.
[0034] In some embodiments, the conductive silicon carbide-based ceramic further includes a binder, a dispersant, and a lubricant, wherein the binder content is 8wt% of the silicon carbide, the dispersant content is 3wt% of the silicon carbide, and the lubricant content is 5wt% of the silicon carbide.
[0035] Binders can reduce the friction between powders, improve powder fluidity, make the material evenly distributed, enhance the formability of powders, prevent powder agglomeration, and improve the strength of green blanks to prevent the blanks from breaking or deforming during transportation or processing. In addition, binders can also promote sintering, reduce sintering temperature, shorten sintering time, and thus improve production efficiency. Binders can be polymers such as phenolic resin, polyvinyl alcohol, and ammonium polyacrylate.
[0036] Adding a dispersant can prevent the powder particles from agglomerating and ensure that they are evenly dispersed in the slurry, thereby improving the uniformity of the green body and the final performance of the ceramic. The dispersant can be a surfactant such as sodium polyacrylate, polyoxyethylene ether, sodium dodecyl sulfate (SDS), or an organic polymer such as polyacrylic acid, polyvinyl alcohol, polyethylene glycol, or a high molecular weight polymer such as polyethyleneimine and polyacrylamide.
[0037] Lubricants can reduce friction between powders and improve the fluidity of powders, which is conducive to uniform mixing and pressing, and reduces cracks and defects during the molding process. Lubricants can be paraffin, stearic acid, polyvinyl alcohol and oleic acid, etc. They can form a lubricating film on the surface of powder particles and reduce adhesion between particles.
[0038] In some embodiments, the conductive silicon carbide-based ceramic further includes boron carbide (B4C) powder, and the content of boron carbide is 2 wt % of silicon carbide.
[0039] Boron carbide can react with silicon carbide at high temperatures to generate a liquid phase, which helps to reduce the sintering temperature, promote bonding between particles, and increase the density of the material, thereby achieving densification, improving the efficiency of the sintering process, and reducing energy consumption. The formation of a liquid phase also helps to fill the gaps between particles, reduce pores, and increase the density and strength of ceramics. Boron carbide can exist as a tiny second phase in the silicon carbide matrix, which helps to hinder the expansion of cracks. Therefore, the addition of boron carbide can also improve the mechanical properties of silicon carbide ceramics, such as bending strength and fracture toughness. Boron carbide also has a certain degree of oxidation resistance, which can protect the performance of silicon carbide ceramics in high temperature environments to a certain extent and reduce oxidation losses. In some applications, it may be necessary to adjust the conductivity of silicon carbide ceramics. The addition of boron carbide can change the conductive properties of ceramics, making them more suitable for specific applications, such as electrospark machining.
[0040] It should be noted that excessive addition of boron carbide may increase the brittleness of the ceramic or reduce other properties. In the embodiment of the present application, the amount of boron carbide added is 2wt% of silicon carbide, which can achieve a better performance balance.
[0041] The method for preparing the conductive silicon carbide-based ceramic of the embodiment of the present application comprises the following steps:
[0042] S100, using silicon carbide powder (particle size 0.5-0.7 micron), multi-walled carbon nanotube powder (particle size ≤ 7 micron), titanium boride powder (particle size 0.8-1.2 micron), tungsten carbide powder (particle size 0.8-1.2 micron), binder, dispersant and lubricant as raw materials, using anhydrous ethanol as solvent, ball milling in a ball mill to obtain slurry. Among them, the content of multi-walled carbon nanotubes is 0.5-3wt% of silicon carbide, the content of titanium boride is 2-12wt% of silicon carbide, the content of tungsten carbide is 2-12wt% of silicon carbide, the content of binder is 8wt% of silicon carbide, the content of dispersant is 3wt% of silicon carbide, the content of lubricant is 5wt% of silicon carbide, and the mass of anhydrous ethanol is the same as the total mass of the four powders of silicon carbide powder, multi-walled carbon nanotube powder, titanium boride powder and tungsten carbide powder.
[0043] In this step, silicon carbide grinding balls are added during ball milling, and anhydrous ethanol in an equal proportion to the powder is added for wet ball milling. The ball milling jar can be a polyurethane ball milling jar. The ball milling time is 24h-48h.
[0044] S200, drying, crushing, sieving and granulating the slurry to obtain powder.
[0045] This step can be carried out by drying in a vacuum drying oven at 90°C-95°C for 6h-8h, and then manually crushing, screening and granulating with a sieve of 80 mesh.
[0046] S300, dry-pressing the powder to obtain a green body.
[0047] This step can be carried out by dry pressing using a hydraulic press.
[0048] S400, sintering the green body in a sintering furnace to obtain a conductive silicon carbide-based ceramic.
[0049] In this step, the green blank can be sintered in an ultra-high temperature vacuum sintering furnace at a sintering temperature of 2150° C.-2200° C. and kept warm for 1-2 hours.
[0050] In some embodiments, 2 wt% boron carbide (B4C) powder of silicon carbide may be added for ball milling in step S100. Boron carbide as a sintering aid can increase material density, improve the efficiency of the sintering process, and increase the density and strength of the ceramic.
[0051] The present application is further described in detail below in conjunction with specific examples. Table 1 shows the components and contents of silicon carbide-based ceramics in various examples and comparative examples.
[0052] Table 1
[0053]
[0054] Embodiment 1:
[0055] S100, using silicon carbide powder (particle size 0.6 micron), multi-walled carbon nanotube powder (particle size ≤ 7 micron), titanium boride powder (particle size 1 micron), tungsten carbide powder (particle size 1 micron), boron carbide powder (particle size 1 micron), phenolic resin binder, amino alcohol dispersant and polyurethane lubricant as raw materials, using anhydrous ethanol as solvent, adding silicon carbide grinding balls in a polyurethane ball mill for wet ball milling, the ball milling time is 48 hours, and obtaining a slurry. The mass of anhydrous ethanol is the same as the total mass of the four powders of silicon carbide powder, multi-walled carbon nanotube powder, titanium boride powder and tungsten carbide powder.
[0056] S200, the slurry is dried in a vacuum drying oven at 90°C for 6 hours, and then manually crushed, sieved and granulated with a sieve of 80 mesh to obtain a powder.
[0057] S300, the powder is dry-pressed by a hydraulic press to obtain a green blank.
[0058] S400, sintering the green body in an ultra-high temperature vacuum sintering furnace at a sintering temperature of 2150° C. and keeping the temperature for 1 hour to obtain a conductive silicon carbide-based ceramic.
[0059] Embodiment 2:
[0060] S100, using silicon carbide powder (particle size 0.6 micron), multi-walled carbon nanotube powder (particle size ≤ 7 micron), titanium boride powder (particle size 1 micron), tungsten carbide powder (particle size 1 micron), boron carbide powder (particle size 1 micron), phenolic resin binder, amino alcohol dispersant and polyurethane lubricant as raw materials, using anhydrous ethanol as solvent, adding silicon carbide grinding balls in a polyurethane ball mill for wet ball milling, the ball milling time is 48 hours, and obtaining a slurry. The mass of anhydrous ethanol is the same as the total mass of the four powders of silicon carbide powder, multi-walled carbon nanotube powder, titanium boride powder and tungsten carbide powder.
[0061] S200, the slurry is dried in a vacuum drying oven at 90°C for 6 hours, and then manually crushed, sieved and granulated with a sieve of 80 mesh to obtain a powder.
[0062] S300, the powder is dry-pressed by a hydraulic press to obtain a green blank.
[0063] S400, sintering the green body in an ultra-high temperature vacuum sintering furnace at a sintering temperature of 2150° C. and keeping the temperature for 1 hour to obtain a conductive silicon carbide-based ceramic.
[0064] Embodiment 3:
[0065] S100, using silicon carbide powder (particle size 0.6 micron), multi-walled carbon nanotube powder (particle size ≤ 7 micron), titanium boride powder (particle size 1 micron), tungsten carbide powder (particle size 1 micron), boron carbide powder (particle size 1 micron), phenolic resin binder, amino alcohol dispersant and polyurethane lubricant as raw materials, using anhydrous ethanol as solvent, adding silicon carbide grinding balls in a polyurethane ball mill for wet ball milling, the ball milling time is 48 hours, and obtaining a slurry. The mass of anhydrous ethanol is the same as the total mass of the four powders of silicon carbide powder, multi-walled carbon nanotube powder, titanium boride powder and tungsten carbide powder.
[0066] S200, the slurry is dried in a vacuum drying oven at 90°C for 6 hours, and then manually crushed, sieved and granulated with a sieve of 80 mesh to obtain a powder.
[0067] S300, the powder is dry-pressed by a hydraulic press to obtain a green blank.
[0068] S400, sintering the green body in an ultra-high temperature vacuum sintering furnace at a sintering temperature of 2150° C. and keeping the temperature for 1 hour to obtain a conductive silicon carbide-based ceramic.
[0069] Embodiment 4:
[0070] S100, using silicon carbide powder (particle size 0.6 micron), multi-walled carbon nanotube powder (particle size ≤ 7 micron), titanium boride powder (particle size 1 micron), tungsten carbide powder (particle size 1 micron), boron carbide powder (particle size 1 micron), phenolic resin binder, amino alcohol dispersant and polyurethane lubricant as raw materials, using anhydrous ethanol as solvent, adding silicon carbide grinding balls in a polyurethane ball mill for wet ball milling, the ball milling time is 48 hours, and obtaining a slurry. The mass of anhydrous ethanol is the same as the total mass of the four powders of silicon carbide powder, multi-walled carbon nanotube powder, titanium boride powder and tungsten carbide powder.
[0071] S200, the slurry is dried in a vacuum drying oven at 90°C for 6 hours, and then manually crushed, sieved and granulated with a sieve of 80 mesh to obtain a powder.
[0072] S300, the powder is dry-pressed by a hydraulic press to obtain a green blank.
[0073] S400, sintering the green body in an ultra-high temperature vacuum sintering furnace at a sintering temperature of 2150° C. and keeping the temperature for 1 hour to obtain a conductive silicon carbide-based ceramic.
[0074] Embodiment 5:
[0075] S100, using silicon carbide powder (particle size 0.6 micron), multi-walled carbon nanotube powder (particle size ≤ 7 micron), titanium boride powder (particle size 1 micron), tungsten carbide powder (particle size 1 micron), boron carbide powder (particle size 1 micron), phenolic resin binder, amino alcohol dispersant and polyurethane lubricant as raw materials, using anhydrous ethanol as solvent, adding silicon carbide grinding balls in a polyurethane ball mill for wet ball milling, the ball milling time is 48 hours, and obtaining a slurry. The mass of anhydrous ethanol is the same as the total mass of the four powders of silicon carbide powder, multi-walled carbon nanotube powder, titanium boride powder and tungsten carbide powder.
[0076] S200, the slurry is dried in a vacuum drying oven at 90°C for 6 hours, and then manually crushed, sieved and granulated with a sieve of 80 mesh to obtain a powder.
[0077] S300, the powder is dry-pressed by a hydraulic press to obtain a green blank.
[0078] S400, sintering the green body in an ultra-high temperature vacuum sintering furnace at a sintering temperature of 2150° C. and keeping the temperature for 1 hour to obtain a conductive silicon carbide-based ceramic.
[0079] Embodiment 6:
[0080] S100, using silicon carbide powder (particle size 0.6 micron), multi-walled carbon nanotube powder (particle size ≤ 7 micron), titanium boride powder (particle size 1 micron), tungsten carbide powder (particle size 1 micron), boron carbide powder (particle size 1 micron), phenolic resin binder, amino alcohol dispersant and polyurethane lubricant as raw materials, using anhydrous ethanol as solvent, adding silicon carbide grinding balls in a polyurethane ball mill for wet ball milling, the ball milling time is 48 hours, and obtaining a slurry. The mass of anhydrous ethanol is the same as the total mass of the four powders of silicon carbide powder, multi-walled carbon nanotube powder, titanium boride powder and tungsten carbide powder.
[0081] S200, the slurry is dried in a vacuum drying oven at 90°C for 6 hours, and then manually crushed, sieved and granulated with a sieve of 80 mesh to obtain a powder.
[0082] S300, the powder is dry-pressed by a hydraulic press to obtain a green blank.
[0083] S400, sintering the green body in an ultra-high temperature vacuum sintering furnace at a sintering temperature of 2150° C. and keeping the temperature for 1 hour to obtain a conductive silicon carbide-based ceramic.
[0084] Comparative Example:
[0085] S100, using silicon carbide powder (particle size 0.6 micron), boron carbide powder (particle size 1 micron), phenolic resin binder, amino alcohol dispersant and polyurethane lubricant of the components and contents shown in Table 1 as raw materials, using anhydrous ethanol as solvent, adding silicon carbide grinding balls in a polyurethane ball mill for wet ball milling for 48 hours to obtain a slurry. The mass of anhydrous ethanol is the same as the total mass of the four powders of silicon carbide powder, multi-walled carbon nanotube powder, titanium boride powder and tungsten carbide powder.
[0086] S200, the slurry is dried in a vacuum drying oven at 90°C for 6 hours, and then manually crushed, sieved and granulated with a sieve of 80 mesh to obtain a powder.
[0087] S300, the powder is dry-pressed by a hydraulic press to obtain a green blank.
[0088] S400, sintering the green body in an ultra-high temperature vacuum sintering furnace at a sintering temperature of 2150° C. and keeping the temperature for 1 hour to obtain a conductive silicon carbide-based ceramic.
[0089] The electrical conductivity and fracture toughness of the silicon carbide-based ceramics prepared in the above examples and comparative examples were tested. The electrical conductivity was tested using a four-probe instrument, and the fracture toughness was tested using a Vickers hardness tester (the method was the Vickers hardness indentation method). The test results are shown in Figure 1 and Figure 2 .
[0090] Figure 1 In the figure, the six data points on the fitting curve correspond to Examples 1 to 6 from left to right. The resistivity of the comparative example is very high, about 10 6 Ω·cm, which is not convenient to illustrate in the figure. It can be seen that after adding the above three second phase materials, the resistivity of silicon carbide-based ceramics is reduced and its conductivity is improved. And the more second phase materials are added, the lower the resistivity.
[0091] Figure 2 In the figure, the first data point is the test result of the comparative example, and the other six data points correspond to Examples 1 to 6 from left to right. It can be seen that after adding the above three second phase materials, the hardness of the silicon carbide-based ceramic is reduced and its fracture toughness is improved. The more second phase materials are added, the higher the fracture toughness.
[0092] Please refer to Table 2 for specific test data.
[0093] Table 2
[0094]
[0095] It should be noted that, unless otherwise specified, the technical terms or scientific terms used in the embodiments of the present application should have the common meanings understood by technicians in the field to which the embodiments of the present application belong.
[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application is described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A conductive silicon carbide-based ceramic, characterized in that: include: Silicon carbide, multi-walled carbon nanotubes, titanium boride and tungsten carbide, wherein the content of the multi-walled carbon nanotubes is 0.5-3wt% of the silicon carbide, the content of the titanium boride is 2-12wt% of the silicon carbide, and the content of the tungsten carbide is 2-12wt% of the silicon carbide.
2. The conductive silicon carbide-based ceramic according to claim 1, characterized in that: The content of the multi-walled carbon nanotubes is 1-1.5wt% of the silicon carbide, the content of the titanium boride is 4-6wt% of the silicon carbide, and the content of the tungsten carbide is 4-6wt% of the silicon carbide.
3. The conductive silicon carbide-based ceramic according to claim 2, characterized in that: The content of the multi-walled carbon nanotubes is 1wt% of the silicon carbide, the content of the titanium boride is 4wt% of the silicon carbide, and the content of the tungsten carbide is 4wt% of the silicon carbide; or, the content of the multi-walled carbon nanotubes is 1.5wt% of the silicon carbide, the content of the titanium boride is 6wt% of the silicon carbide, and the content of the tungsten carbide is 6wt% of the silicon carbide.
4. The conductive silicon carbide-based ceramic according to claim 1, characterized in that: The conductive silicon carbide-based ceramic further includes a binder, a dispersant and a lubricant, wherein the content of the binder is 8wt% of the silicon carbide, the content of the dispersant is 3wt% of the silicon carbide, and the content of the lubricant is 5wt% of the silicon carbide.
5. The conductive silicon carbide-based ceramic according to claim 1, characterized in that: The conductive silicon carbide-based ceramic further includes boron carbide, and the content of the boron carbide is 2 wt % of the silicon carbide.
6. A method for preparing a conductive silicon carbide-based ceramic, characterized in that: The steps include: S100, using silicon carbide powder, multi-walled carbon nanotube powder, titanium boride powder, tungsten carbide powder, a binder, a dispersant and a lubricant as raw materials, using anhydrous ethanol as a solvent, and ball milling in a ball mill to obtain a slurry, wherein the content of the multi-walled carbon nanotube is 0.5-3wt% of the silicon carbide, the content of the titanium boride is 2-12wt% of the silicon carbide, the content of the tungsten carbide is 2-12wt% of the silicon carbide, the content of the binder is 8wt% of the silicon carbide, the content of the dispersant is 3wt% of the silicon carbide, the content of the lubricant is 5wt% of the silicon carbide, and the mass of the anhydrous ethanol is the same as the total mass of the four powders of the silicon carbide powder, the multi-walled carbon nanotube powder, the titanium boride powder and the tungsten carbide powder; S200, drying, crushing, sieving and granulating the slurry to obtain ceramic powder; S300, dry-pressing the ceramic powder to obtain a green body; S400, sintering the green blank in a sintering furnace to obtain a conductive silicon carbide-based ceramic.
7. The method according to claim 6, characterized in that The particle size of the silicon carbide powder is 0.5-0.7 microns, the particle size of the multi-walled carbon nanotube powder is less than or equal to 7 microns, the particle size of the titanium boride powder is 0.8-1.2 microns, and the particle size of the tungsten carbide powder is 0.8-1.2 microns.
8. The method according to claim 6, characterized in that The content of the multi-walled carbon nanotubes is 1wt% of the silicon carbide, the content of the titanium boride is 4wt% of the silicon carbide, and the content of the tungsten carbide is 4wt% of the silicon carbide; or, the content of the multi-walled carbon nanotubes is 1.5wt% of the silicon carbide, the content of the titanium boride is 6wt% of the silicon carbide, and the content of the tungsten carbide is 6wt% of the silicon carbide.
9. The method according to claim 6, characterized in that In the S100, boron carbide is also added during ball milling in the ball mill, and the content of the boron carbide is 2wt% of the silicon carbide.
10. The method according to claim 6, characterized in that The ball milling time in S100 is 48h; In the S200, the slurry is dried in a vacuum drying oven at 90° C. for 6 hours, and then manually crushed, sieved and granulated, with a sieve of 80 meshes, to obtain ceramic powder; In the S400, the green blank is sintered in an ultra-high temperature vacuum sintering furnace at a sintering temperature of 2150° C. and kept at this temperature for 1 hour to obtain a conductive silicon carbide-based ceramic.